2013
DOI: 10.1093/carcin/bgt020
|View full text |Cite
|
Sign up to set email alerts
|

LGR5 promotes survival in human colorectal adenoma cells and is upregulated by PGE 2 : implications for targeting adenoma stem cells with NSAIDs

Abstract: Cyclooxygenase-2 is overexpressed in the majority of colorectal tumours leading to elevated levels of prostaglandin E2 (PGE2), promoting many hallmarks of cancer. Importantly, PGE2 is reported to enhance Wnt/β-catenin signalling in colorectal carcinoma cells and in normal haematopoietic stem cells where it promotes stem cell function. Although Wnt signalling plays a crucial role in intestinal stem cells, the relationship between PGE2 and intestinal stem cells is unclear. Given that the key intestinal cancer st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 42 publications
8
65
1
Order By: Relevance
“…Our results suggest that LGR5 is involved in the growth and progression of CRC and it may be an important biological marker of its invasion and metastasis. Our results are consistent with previous studies proving that overexpression of LGR5 was associated with poor prognosis in CRC [26][27][28][29] . The current results also are consistent with studies done in other organs stating that LGR5 overexpression is associated with poor prognosis and metastasis-initiating potentials in breast cancer, glioblastoma, lung cancer and esophageal adenocarcinoma [30][31][32][33] .…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggest that LGR5 is involved in the growth and progression of CRC and it may be an important biological marker of its invasion and metastasis. Our results are consistent with previous studies proving that overexpression of LGR5 was associated with poor prognosis in CRC [26][27][28][29] . The current results also are consistent with studies done in other organs stating that LGR5 overexpression is associated with poor prognosis and metastasis-initiating potentials in breast cancer, glioblastoma, lung cancer and esophageal adenocarcinoma [30][31][32][33] .…”
Section: Discussionsupporting
confidence: 93%
“…These reports are in agreement with other experiments indicating a significant decrease in survival [203], drug resistance [204], proliferation, migration, and tumorigenic abilities [205] of CRC cells upon LGR5 knockdown. Moreover, clinical analysis demonstrated enhanced expression of LGR5 in CRC tissues, although its association with clinicopathological features is controversial; based on a number of reports, LGR5 expression was correlated to progression, lymph node and distant metastasis, recurrence, clinical outcomes, and survival rate of CRC [197,198,204,[206][207][208][209][210][211][212], whereas other studies indicated an inverse correlation [213] or no association [214,215] between LGR5 upregulation and CRC progression.…”
Section: Colon and Rectumsupporting
confidence: 93%
“…In addition, NANOG-siRNA transfection induced apoptosis and enhanced chemosensitivity of ESCC cells [106], similar to downregulation of SOX2 with siRNA, which reduced colony forming, drug resistance, and in vivo tumorigenicity of gastric CSCs [149]. Reports have also demonstrated that RNAi targeting LGR5 in CRC-SCs enhanced drug sensitivity of cells [202,204], while decreased their survival, proliferation [203][204][205], migration, and tumorigenic [205] abilities.…”
Section: Implications Of Cscs In Developing Targeted Therapies For DImentioning
confidence: 86%
“…Interestingly, the anti-colon cancer stem cell effect of NSAIDs is mediated through both COX-dependent and -independent pathways (Moon et al, 2014). Paraskeva has elegantly linked PGE 2 with colon adenoma and carcinoma stem cells by showing that the former promotes the survival of the latter (Al- Kharusi et al, 2013). Although it appears that the definitive mechanism by which NSAIDs prevent CRC is far from complete, it is fair to state that its broad outlines have been identified and a deeper understanding should be forthcoming.…”
Section: Evolving Role Of Nsaids In Colon Cancer Preventionmentioning
confidence: 99%